설비 이상탐지를 위한 딥러닝 알고리즘 개발 - 김민희(Min-Hee Kim); 진교홍(Kyo-Hong Jin) (한국정보통신학회논문지, 2022)
A malfunction or breakdown of a manufacturing facility leads to product defects and the suspension of production lines, resulting in huge financial losses for manufacturers. Due to the spread of smart factory services, a large amount of data is being collected in factories, and AI-based research is being conducted to predict and diagnose manufacturing facility breakdowns or manufacturing site efficiency. However, because of the characteristics of manufacturing data, such as a severe class imbalance about abnormalities and ambiguous label information that distinguishes abnormalities, developing classification or anomaly detection models is highly difficult. In this paper, we present an deep learning algorithm for anomaly detection of a manufacturing facility using reconstruction loss of CNN-based model and ananlyze its performance. The algorithm detects anomalies by relying solely on normal data from the facility's manufacturing data in the exclusion of abnormal data. 제품을 생산하는 설비의 고장이나 이상 현상은 곧 제품의 결함 및 생산라인 가동 중단으로 이어져 제조 업체의 막대한 경제적 손실의 원인이 된다. 스마트팩토리 서비스의 확산으로 공장에서 많은 양의 데이터가 수집됨에 따라, 이를 활용하여 제조 현장의 효율이나 제조 설비의 고장 예측 및 진단을 위한 인공지능 기반의 연구가 활발히 이어지고 있다. 하지만 정상과 이상을 구분 짓는 레이블 정보가 명확하지 않고 이상에 대한 극심한 클래스 불균형을 가지는 제조 데이터의 특징으로 인하여 분류 모델이나 이상탐지 모델의 개발에는 큰 어려움이 존재한다. 본 논문에서는 딥러닝 모델의 재구성 손실값을 이용하여 제조 설비의 이상탐지를 위한 딥러닝 알고리즘을 제안하고 성능을 분석하였다. 해당 알고리즘은 이상 데이터를 제외한 설비의 제조 데이터, 즉 정상 데이터에만 의존하여 이상을 감지한다.